The Ox’s Tail: Reading Frank Herbert’s Dune as a Zen Buddhist Koan - Smith, Tara B. M. (Journal for the academic study of religion, 2024)
Frank Herbert’s Dune novels are suffused with Zen concepts that support his belief in ecology in two major ways. Firstly, Herbert’s reflections on the novels in key interviews make explicit that he consciously uses the trope of Zen philosophy to explore and prosecute the case for environmentalism and ecology. And secondly, the series is replete with structural elements and literary motifs that are a homage to core Zen teachings and reinforce the ecological themes of the work. Thematic explorations of the importance of balance between the spiritual and physical elements of human life are represented throughout the series, and the cyclical plot structures reinforce the core Zen belief in the continuous lifecycle of life, death, and rebirth. Further, plot devices throughout the works operate like Zen koans, intricate riddles aimed at challenging the reader to question their assumptions and beliefs. A central koan throughout the series speaks to the paradox of a humanity that is utterly reliant on mother nature for survival and solace, whilst simultaneously being a humanity that is threatening the survival and solace of nature. His didactic style of Zen teaching through koan teachings in the novels imparts lessons around students/readers developing ideas for themselves, thinking differently and ultimately breaking free of passive readership—forcing the responder to enter a dialogue with the novel and the narrator. Herbert draws on the teachings of Zen Buddhism in the Dune series to explore his obvious love of nature, and his fascination with ecological systems, feedback loops, and the interconnectedness and interdependence of all living organisms.